Effect of dynamic thoracolumbar orthosis on Scheuermann's kyphosis angle - Fahime Sadat Abtahi; Behnam Hajji Aghaee; Mohammad Reza Keihani (Vesnu Publications, 2011)
Abstract Introduction: this study was aimed at assessing the effect of a new thoracolumbar orthosis on patients with Scheuermann's kyphosis referred to Iran medical university of Tehran in collaboration with a clinic of technical ortopedea in Isfahan. Material and method: This new version of orthosis had a dynamic system as compared to previous ones which enabled the spine to extend. a questionnaire along with a radiographic picture of spine were used for evaluating the efficacy of this kind of orthosis. Measurement of the Cobb angles was also performed in 3 stages. Results: mean difference correction of Cobb angle for dynamic thoracolumbar orthosis was 29.5% and mean difference correction of Cobb angle for Milwaukee was 35.5%. Difference of Cobb angle was measured by Cobb angle before application orthosis and by second month of its usage. Conclusion: results showed that not only was the new dynamic thoracolumbar orthosis effective in orthosis correction and improved Cobb angle at 2 months follow-up but also it was well accepted by the user thanks to its beautiful structure. Key words: Dynamic thoracolumbar othosis, scheuermann kyphosis, orthosis correction